Service Design of Implementation Primary Health Care Management Model Service â€œAndalâ€ in PG Kebonagung Polyclinic, Malang District - Sani, Yasir; Aknuranda, Ismiartha; Tolle, Herman (Faculty of Computer Science (FILKOM) Brawijaya University, 2018)
The concept of Primary Health Service Management Model â€œAndalâ€ (LKP Andal) in Indonesia was initiated by the Public Health Association of Brawijaya University (IKEMAS UB) to solve the health service management problem in Indonesia. LKP Andal was piloted into a first-level organization that provide the health service/facility in PG Kebonagung polyclinic in Malang district.This research uses a service design approach to explore the problems and this study also provide a service solution to the LKP Andal implementation in IT perspective that suits to the organization characteristics as an entirely service delivery process support. As the result, this study has explored 23 main problems of the entirely service delivery process and also resulted 4 service solution ideas which were visualized using Service Journey Modelling Language (SJML) to acquire more detailed images and they can become the standard communication among stakeholders.